PERCEPTIONS OF EASY OF USE, BENEFITS, AND RISKS OF THEIR EFFECT ON INTEREST IN SHOPEE PAYLATER USING THE SHOPEE MARKETPLACE AS A MEDIATION VARIABLE - Rifa’i, Muhamad; Difa Alabror; Warter Agustim (SEAN Institute, 2022)
This study aims to determine the effect of perceived ease of use, benefits, and risks on interest in using shopee paylater, with the use of shopeepay as a mediating variable, because the importance of something that can trigger individual interest in something that already has an image is avoided. This type of research uses quantitative research with a total of 100 respondents through purposive sampling. The results of the study indicate that there is a direct and indirect positive and significant effect of perceived ease of use, benefits, and risks on Shopee PayLater, and through the use of Shopeepay, with a t-count > t-table, and the significance of t < 0. And the effect value indirect which is greater than the value of the direct influence between variables. So that all research hypotheses can be accepted.